Influenza D virus in cattle (review) - S. V. Koteneva; A. G. Glotov; T. I. Glotova; A. V. Nefedchenko (Ветеринария сегодня)
The influenza D virus was first detected and identified in 2011. The overall amino acid sequence of influenza D virus shares approximately 50% identity with that of influenza C virus, suggesting that both viruses had a common ancestor. Cattle is considered to be the primary natural reservoir for influenza D virus. The involvement of this virus into the bovine respiratory disease complex has been confirmed. The virus causes mild to moderate disease in calves and replicates in both the upper and lower respiratory tracts, promoting bronchopneumonia. The influenza D virus can be transmitted by contact or aerosol over short distances, has a high transmission rate and can potentiate the effects of other respiratory pathogens. There are currently no vaccines or specific treatment for influenza D virus. This virus can replicate and be transmitted by direct contact in ferrets and guinea pigs, which are surrogate models of human influenza infection, as well as in well-differentiated human airway epithelial cells (hAECs). Currently five distinctive lineages of influenza D virus have been identified, co-circulating in worldwide bovine and pig populations that may facilitate genetic re-assortment between different viral strains. The virus has a zoonotic potential, and if its pathogenicity for humans changes, its importance for public health will be great. Very high seropositivity rates among persons working with cattle in the USA and Italy have been reported. There is no data in the available literature on the circulation of the influenza D virus in the Russian Federation. Research is needed to study this new virus, as well as monitoring of the virus spread and circulation in our country to understand its role in bovine respiratory disease complex and its zoonotic potential.